Evaluation of the Efficiency of Treatment for Massive Obstetric Hemorrhage - S. V. Barinov; I. V. Medyannikova; V. T. Dolgikh (Общая реаниматология)
Objective: to evaluate the efficiency of therapy for massive obstetric hemorrhage, by applying thromboelastography (TEG). Subjects and methods. Sixty six patients with massive obstetric hemorrhage who were divided into two groups: a study (A; n=37) and comparison (B; n=29) groups were examined. A control group (C; n=30) comprised women with physiological blood loss during labor. The efficiency of TEG was evaluated from the volume of blood loss and the frequency of hysterectomy.Results. Fibrin clot density, MA have the highest prognostic capacity to identify the risk of massive obstetric hemorrhage [AUC=0.83 (95% CI 0.79—0.87); р=0.001]. A therapeutic and diagnostic set for massive obstetric hemorrhage, by applying TEG, can reduce the number of hysterectomies by 3. 1 times (p=0.02), the volume of blood loss by 1.3 times (p=0.03), and the use of fresh frozen plasma by 2.0 times (p=0.01). Conclusion. Rapid evaluation of the blood coagulation system, by using a TEG® 5000 device (Haemoscope Corp., USA) makes it possible to perform timely pathogenetic sound therapy, to prevent a critical condition, and to implement organ-sparing tactics.